2021
DOI: 10.1136/bcr-2020-240937
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Leydig cell tumor and postmenopausal hirsutism with signs of virilisation

Abstract: A 71-year-old woman was referred to the endocrinology clinic to investigate postmenopausal hirsutism with 10 years of evolution. She had history of regular menses and menopause with 50 years old. Physical examination showed a male pattern facies, deepening of the voice, androgenic alopecia and hirsutism with a score of 23 according to the modified Ferriman-Gallwey scale. Testosterone and androstenedione were increased. Transvaginal ultrasound, abdominal and pelvic CT showed uterine fibroids with no pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Wesolowska et al reported a 64-year-old postmenopausal woman with an ovarian tumor who developed advanced AGA and progressive hirsutism within 3 years [ 49 ]. Ferrinho Catia et al reported a similar case [ 51 ]. These reports indicate that increased androgen levels may lead to the appearance of AGA in androgen-secreting tumors.…”
Section: Cancermentioning
confidence: 91%
See 1 more Smart Citation
“…Wesolowska et al reported a 64-year-old postmenopausal woman with an ovarian tumor who developed advanced AGA and progressive hirsutism within 3 years [ 49 ]. Ferrinho Catia et al reported a similar case [ 51 ]. These reports indicate that increased androgen levels may lead to the appearance of AGA in androgen-secreting tumors.…”
Section: Cancermentioning
confidence: 91%
“…Recently, some scholars have proposed that AGA is also related to cancer, but the results of these studies are controversial [ 46 51 ]. A meta-analysis assessed the relationship between cancer incidence or cancer-specific mortality and AGA categories using retention odds ratios (OR) or hazard ratios (HR) with 95% confidence intervals (CI).…”
Section: Cancermentioning
confidence: 99%
“…Luteinizing hormone stimulation maintains ovarian androgen secretion in postmenopause [ 1 , 2 ]. Despite the physiological hormone processes in menopause, the presence of true virilisation characteristics such as alopecia, hirsutism, acne, deepening of the voice, or clitoromegaly must be analysed cautiously, as these disorders can be caused by various non-tumorous or tumorous conditions with androgen hyperproduction [ 1 , 2 , 3 , 4 ]. Identifying the precise cause of hyperandrogenism can be a complex task, requiring a comprehensive approach that combines clinical assessment, laboratory testing, imaging techniques and, in certain cases, postoperative histopathological examination.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, hormonally active tumors account for about 5% of all ovarian masses [ 2 , 3 , 4 ], and the incidence of steroid cell tumors is less than 0.1% of all ovarian neoplasms [ 5 ]. Notably, there are associations between ovarian LCTs and gynecological cancer [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%